Etos Kepemimpinan Yang Adil dan Amanah: (Pendekatan Tafsir Maudhu‘i terhadap Ayat-Ayat Quranic Leadership) - bana; Bashori (Jurnal Al I'jaz, 2026)
This study aims to explore the concept of justice and trustworthiness for leadership in the Qur'an through a tafsir maudhu'i (thematic exegesis) approach. In the midst of contemporary socio-political dynamics marked by ethical crises of leadership, this research is relevant to explore Qur'anic values that can serve as a foundational framework for building integrity-based and justice-oriented leadership. Using a qualitative method, this study conducts a thematic analysis of Qur'anic verses to explain the principles of amanah (trustworthiness), adalah (justice), prophetic ethics, and consultation (shura). The primary data are drawn from selected verses of the Qur'an, interpreted through classical and contemporary exegetical works such as Tafsir al-Tabari, al-Qurtubi, al-Mizan, and Fi Zilal al-Qur'an. The findings reveal that Qur'anic leadership is constructed upon four key pillars: trustworthiness, justice, prophetic role model, and consultative legitimacy. Each of these explanations encompasses various dimensions and indicators reflecting the universal values of the Qur'an. These values are applicable to contemporary models of public leadership. The study concludes that the tafsir maudhu'i approach offers an ethical and spiritual framework for shaping leadership that is not only effective but also grounded in values and social justice consistent with Qur'anic principles.